Synthesis and Structure of a Trans-oxpn-bridged Binuclear Copper(II) Complex - Hu, Nai-Liang; Bi, Jian-Hong; Huang, Zi-Xiang; Shen, Yu-Hua (Asian Journal of Chemistry, 2016)
A novel complex [(CuL)2(trans-oxpn)](ClOnothing4)2·2DMF, where oxpn is the dianion of N,N'-bis-(3-aminopropyl)oxamide and L = 1,10-N,N-fluorenone, was synthesized by the reaction of Cu(ClO4)2·6H2O with Cu(oxpn) and L in the mixed solvent and characterized by IR spectra and elemental analysis. A single-crystal X-ray study shows that the complex is a four coordinated copper(II) with a plane square environment compound. The crystal is triclinic, space group p-1, with unit cell parameters: a = 9.03960(10) Å, b = 11.0938(3) Å, c = 11.3864(3) Å, a = 106.97(10)°, b = 97.8450(10)°, g = 90.1180 (10)°, V = 1080.87(4) Å3, Z = 1, Mr = 1036.78, Dc=1.593 Mg/m3, μ = 1.185 mm–1, F(000) = 532, T = 293(2) K, R = 0.0548, wR = 0.1323 for 3707 reflections with I > 2s(I).